THE ROLE OF DIGITAL TRUST IN DRIVING REPURCHASE INTENTION ON TIKTOK SHOP IN INDONESIA - Mardi Putra, Christian Immanuel; Widoretno, Esa Panganti (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The rapid advancement of technology has significantly impacted business activities, leading to the rise of e-commerce. Social commerce (S-commerce) integrates social media into e-commerce, offering new opportunities in developing markets like Indonesia. This study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between perceived technology, security, reputation, risk, S-commerce knowledge, and prior online purchase experience on online trust and repurchase intention. Findings reveal that perceived technology and reputation positively influence online trust, while perceived risk has a negative effect. Online trust mediates the effect of perceived technology on repurchase intention but not prior online purchase experience. The study emphasizes the role of trust in enhancing consumer participation in S-commerce.